Analyzing the influence of structural changes on CO2 emissions in OECD countries: Employing panel cointegration techniques - Kahouli, Zohra; Hasni, Radhouane; Ben Jebli, Mehdi (Center of Biomass & Renewable Energy (CBIORE), 2025)
Structural transformations in OECD countries significantly influence carbon dioxide (CO2) emissions, affecting economic and social dimensions. These transformations encompass changes in industrial composition, technological progress, energy consumption patterns, and policy frameworks. This research investigates the impact of such structural shifts on CO2 emissions across a panel of 38 OECD countries between 2000 and 2021, using panel cointegration techniques to ensure robust analysis. The study confirms the presence of cross-sectional dependence among countries and establishes long-run cointegration relationships. Results from Fully Modified Ordinary Least Squares (FMOLS) and Dynamic Ordinary Least Squares (DOLS) models indicate that renewable energy, advancements in information and communication technology, and structural changes significantly reduce CO2 emissions. In contrast, economic growth, reliance on non-renewable energy, and institutional quality are linked to higher emissions. However, estimates derived from Panel-Corrected Standard Errors (PCSE) and Mean Group Panel (MGP) methods differ from those of FMOLS and DOLS, underscoring potential methodological variances in evaluating these relationships. This study highlights the pivotal role of structural changes in emission reduction strategies, while also emphasizing the importance of methodological choices in policy analysis. The findings provide valuable insights for policymakers aiming to align economic growth with environmental sustainability within OECD countries. Moreover, the research stresses the necessity of incorporating structural changes into long-term climate strategies to ensure their effectiveness. Future studies could expand the analysis by integrating more recent data and exploring non-linear relationships to refine policy recommendations further.